Bimetallic ruthenium–nickel alloy nanostructure supported on nickel foam for efficient alkaline hydrogen evolution at large current density. Issue 2 (5th December 2022) - Mao, Xiaoqing; Liu, Zhihang; Lin, Changqing; Li, Jiawang; Shen, Pei Kang
Abstract : A ruthenium–nickel alloy nanostructure exhibits a low overpotential and excellent activity stability for the hydrogen evolution reaction in 1 M KOH. Abstract : Developing low-cost and efficient catalysts for hydrogen evolution is of great significance to solve the human energy crisis. In this work, ruthenium–nickel alloy is synthesized by a solvothermal method. The ruthenium–nickel alloy shows distinguished catalytic performance and durability for the hydrogen evolution reaction in alkaline solution (1 M KOH). Only 21, 76, 222 and 323 mV overpotentials are required to reach current densities of 10, 100, 1000 and 2000 mA cm −2 . After 150 hours of a durability test at a current density of −400 mA cm −2, the alloy also shows outstanding durability. Density functional theory (DFT) further shows that ruthenium–nickel alloy composites can optimize the reaction barrier of alkaline hydrogen evolution. This study provides a valuable method for developing high-performance and low-price alloy catalysts for hydrogen evolution.